Experimental Substantiation of the Possibility to Use Finite Cell Line CHO-K1 for Determination of Specific Activity of Components of Chemical Cholera Vaccine - O. S. Durakova; O. V. Gromova; A. V. Gaeva; S. V. Generalov; L. F. Livanova; O. D. Klokova; O. A. Volokh (Проблемы особо опасных инфекций, 2020)
Objective was to experimentally substantiate the possibility to use the finite cell line CHO-K1 for measuring specific activity of cholera toxin and component of the vaccine choleragen-anatoxin in the process of chemical cholera vaccine manufacturing. Materials and methods. The studies involved the finite cell line CHO-K. The registration of results of bio-indication method was performed visually with the help of inverted microscope and photometrically - in colorimetric test for the assessment of metabolic activity of the cells at the wave length of 595 nm. Results and discussion. The proposed method allows for determining the toxin-production activity of Vibrio cholerae 569B strain during submerged cultivation in bioreactor and specific activity of choleragen-anatoxin by anatoxin binding measuring using cell cultures. The results correlate with the data obtained using intradermal Craig’s technique, GM1-ELISA and radial passive immune hemolysis (RPIH). Introduction of cell culture method into practice will provide for significant decrease in the volumes of usage of animals at the stages of manufacturing of chemical bivalent cholera vaccine.